Anaphora processing and applications 8th Discourse Anaphora and Anaphor Resolution Colloquium, DAARC 2011, Faro, Portugal, October 6-7, 2011. Revised Selected Papers - Hendrickx, Iris; Lalitha Devi, Sobha; Branco, António; Mitkov, Ruslan (Springer eBook., 2011)
This book constitutes the refereed proceedings of the 8th Discourse Anaphora and Anaphor Resolution Colloquium, DAARC 2011, held in Faro, Portugal, in October 2011. The 16 revised full papers presented were carefully reviewed and selected from 45 initial submissions. The papers are organized in topical sections on computational resolution methodology and systems; language analysis and representation; and human processing and performance.